Hunger in French Western Africa : Colonial Investigations and Representations (1920-1960) - (:unkn) unknown (My University, 2009)
This article focuses on the way Hunger was constructed as a specific colonial knowledge in French Western Africa from 1920 to 1960. During the Interwar period, there was a widening gap between the claim to improve the food standards of colonial subjects and the knowledge most administrators had on indigenous eating habits. Food intakes were measured through productive indicators rather than nutritional criteria. After World War Two, in the context of colonial legitimacies crisis, the colonial administration produced new knowledge on indigenous standards of living and more specifically on eating habits. There was no real improvement of the knowledge on Hunger before the independences but at least, this issue became an object of investigation and of measurement.
Keywords: African Research